Dampak pembelajaran online pada kursus bola basket: Studi desain eksperimental sejati pada siswa olahraga - Hidayatullah, Fajar; Yuli Handayani, Heni; Khozanah Ilmah, Nur; Nisa, Hoirun (Universitas Nusantara PGRI Kediri, 2024)
This study explores the implementation of online learning for basketball courses at STKIP PGRI Bangkalan compared to offline basketball courses. Employing a true experimental design with a posttest-only control setup, the research gathers data through pretest and posttest scores. The study ensures validity through expert validation and assesses reliability using product-moment correlation. Normality tests are performed with the one-sample Kolmogorov-Smirnov test, while differences are evaluated using an independent sample t-test. This research reveals significant differences between online and offline learning environments. The analysis highlights a decrease in performance during online courses with a mean difference of 9.29870, underscoring the challenges faced by students in adapting to online learning platforms. The study contributes valuable insights into the effectiveness of online learning in physical education, providing a basis for future educational strategies and interventions.